2013
DOI: 10.11118/actaun201361051289
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of rapeseed expeller for carp (Cyprinus carpio) diets

Abstract: KUKAČKA VLADIMÍR, JIRÁSEK JIŘÍ, KOPP RADOVAN, MAREŠ JAN: The utilization of rapeseed expeller for carp (Cyprinus carpio) diets. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 5, pp. 1289-1295 Production eff ectiveness of rapeseed stamping in the common carp fodder was attested in the controlled conditions of recirculation system with the absence of natural food. 4 isonitrogenous (31.5% NS) and isoenergetic (17.3 MJ GE.kg ) diet with diff erent (35 and 40%) unmodifi ed (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In contrast, Rumsey et al (1992) observed that there was no negative effect on feed intake when rainbow trout were fed a diet where 500 g kg -1 of FM was replaced with brewer's yeast. Kukačka and Mareš (2008) showed that the substitution with 15 g kg -1 corn DDGS generated better growth than 30 g kg -1 corn DDGS in the diets of common carp but no adverse effects were found in the fish fed 30% DDGS compared with the control fish fed diet. Nile tilapia has shown no reduction in growth and feed utilization effects when fed up to a 500 g kg -1 substitution of FM with brewers waste (Zerai et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, Rumsey et al (1992) observed that there was no negative effect on feed intake when rainbow trout were fed a diet where 500 g kg -1 of FM was replaced with brewer's yeast. Kukačka and Mareš (2008) showed that the substitution with 15 g kg -1 corn DDGS generated better growth than 30 g kg -1 corn DDGS in the diets of common carp but no adverse effects were found in the fish fed 30% DDGS compared with the control fish fed diet. Nile tilapia has shown no reduction in growth and feed utilization effects when fed up to a 500 g kg -1 substitution of FM with brewers waste (Zerai et al, 2008).…”
Section: Discussionmentioning
confidence: 96%